2011
DOI: 10.1002/app.34493
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2 epoxy nanocomposites by ultrasonic dispersion and resulting properties

Abstract: Nanocomposites gained more and more importance in the last few years because of their improved performance over the neat polymer matrix, that is, toughness and stiffness can be enhanced simultaneously by the addition of nanoparticles. However, the dispersion of these particles in the matrix remains a big challenge. In this study, two types of TiO 2 nanoparticles were dispersed in two different epoxy resins by means of ultrasound. The particle size development in dependence on the dispersion time was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…When zeolite was added the viscosity of the casting solution increased from 2499 to 3233 mPa · s for an untreated solution containing 10 wt % of NaA zeolite. A similar phenomenon has been reported by Bittmann et al They found that adding TiO 2 nanoparticles in epoxy resin caused a strong increase in viscosity up to 8 Pa · s for RM 300 and up to 10 Pa · s for RM 400, from 0.02 Pa · s. We speculated that the negatively charged carboxyls of PAAS bonded with Na + in the NaA zeolite strongly and thus formed a local supersaturation microenvionment. Moreover, the strong electric field resulting from the high concentration of negatively charged carboxyls favored the interaction with the positively charged NaA zeolite.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…When zeolite was added the viscosity of the casting solution increased from 2499 to 3233 mPa · s for an untreated solution containing 10 wt % of NaA zeolite. A similar phenomenon has been reported by Bittmann et al They found that adding TiO 2 nanoparticles in epoxy resin caused a strong increase in viscosity up to 8 Pa · s for RM 300 and up to 10 Pa · s for RM 400, from 0.02 Pa · s. We speculated that the negatively charged carboxyls of PAAS bonded with Na + in the NaA zeolite strongly and thus formed a local supersaturation microenvionment. Moreover, the strong electric field resulting from the high concentration of negatively charged carboxyls favored the interaction with the positively charged NaA zeolite.…”
Section: Resultssupporting
confidence: 88%
“…As shown in Figure , when the ultrasonication time was not too long, the membrane morphology was more homogenous. From the above discussion about viscosity, the proper viscosity was obtained when the ultrasonic time lay between 1.0 and 1.5 h, which is beneficial to the dispersion of zeolite in the PAAS matrix . However, the membrane morphology became rough and formed a lamellar morphology when the casting solution was ultrasonicated for 2.5 h.…”
Section: Resultsmentioning
confidence: 94%
“…The bands at 2931 and 1452 cm À1 are associated with the C-H asymmetric stretching and bending vibration in methylene group, as well as 2874 and 1376 cm À1 are C-H symmetric deformation in methyl group [24,25]. The bands at 1735 and 2238 cm À1 are respectively attributed to the stretching vibration of carbonyl (C]O) [26e28] and cyano (C^N) [29,30]. Moreover, the absorption peaks at 703 and 1602 cm À1 are indicative of single substituted phenyl ring and vibration of benzene skeletal ring, respectively [31].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Dynamic light scattering (DLS) measurements were performed at 25.0°C( Malvern Zetasizer Nano Z, laser wavelength 534 nm). While this technique is best suited for the measurement of the diameters of well-dispersed spherical primary particles with sizes of 1 to 1000 nm [13], it has also been successfully used for quantifying agglomerate sizes [14][15][16][17][18]. EtOH suspensions were diluted with additional EtOH 1:10 (resulting particle volume fraction u p % 5 Â 10 À 6).…”
Section: Characterizationmentioning
confidence: 99%